An Experimental Study of Diagnostic Assessment Using Florence Littauer’s Personality Theory in Teaching Geography through the TaRL Approach - Alfiani Dwi Astuti; Erin Parastika; Rahmawati Nurkarima; Eko Hariyadi; Gaby Nanda Kharisma (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2026)
This experimental study investigates the impact of a digital diagnostic evaluation, grounded in Florence Littauer's personality theory, on enhancing learning outcomes within the Teaching at the Right Level (TaRL) framework. TaRL differentiates students' personality types sanguine, choleric, melancholy, and phlegmatic from their learning levels and seeks to address both aspects. This research aims to align instruction with both learning traits and academic preparedness. The research employs the Shapiro-Wilk normality test, paired-sample t-test, and N-gain analysis to evaluate outcomes. The study was conducted at MAN 1 Kolaka with Class X1 Al-Bukhori Muslim, employing diagnostic evaluations featuring narrative sentences for each personality type, in addition to pre- and post-tests. The Shapiro-Wilk test produced a significance of 0.06 for the pre-test and 0.09 for the post-test, indicating a normal data distribution. The paired-samples t-test (sig=0.001 0.05) indicated significant alterations in learning outcomes, while the N-Gain score (0.75 0.70) demonstrated substantial effectiveness. The results indicate that this diagnostic method can assist TaRL; however, additional validation is required.